(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The significance of linking pneumatic transport pipes in cotton ginning factories is discussed in the article. Consideration is given to how air duct sealing affects fan performance and energy usage.